Morphological evolution of the bivalve Ptychomya through the Lower Cretaceous of Argentina - Milla Carmona, Pablo Sebastián (2018)
The complex morphological evolution of the bivalve Ptychomya throughout the well-studied Agrio Formation in the Neuquén Basin (west-central Argentina, lower/upper Valanginian-lowest Barremian) constitutes an ideal opportunity to study evolutionary patterns and processes occurring at geological timescales. Ptychomya is represented in this unit by four species, the morphological variation of which needs to be temporally assessed to obtain a thorough picture of the evolution of the group. Here we use geometric morphometrics to measure variation in shell outline, ribbing pattern, and shell size in these species. We bracket the ages of our samples using a combination of ammonoid biostratigraphy and absolute ages and study the anagenetic pattern of evolution of each trait by means of paleontological time-series analysis and change tracking. We find that evolution in Ptychomya is mostly speciational, as the majority of traits show stasis, with the exceptions of shell size in P. coihuicoensis and shell outline in P. windhauseni, which seem to evolve directionally toward larger and higher shells, respectively. Ptychomya displays changes in its average morphology and disparity, which are the result of amixture of taxonomic turnover and mosaic evolution of traits. Pulses of speciation would have been triggered by ecological opportunity, as they occur during the recovery of shallow-burrowing bivalve faunas after dysoxic events affecting the basin. On the other hand, the presence of directional patterns of evolution in P. coihuicoensis and P. windhauseni seems to be the result of a general shallowing-upward trend observed in the basin during the upper Hauterivian-lowest Barremian, as opposed to the cyclical paleoenvironmental stability inferred for the early/late Valanginian-early Hauterivian, which would have prompted stasis in P. koeneni and P. esbelta.